2018
DOI: 10.1016/j.phrs.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ER-mitochondria contacts by Parkin via Mfn2

Abstract: Parkin, an E3 ubiquitin ligase and a Parkinson's disease (PD) related gene, translocates to impaired mitochondria and drives their elimination via autophagy, a process known as mitophagy. Mitochondrial pro-fusion protein Mitofusins (Mfn1 and Mfn2) were found to be a target for Parkin mediated ubiquitination. Mfns are transmembrane GTPase embedded in the outer membrane of mitochondria, which are required on adjacent mitochondria to mediate fusion. In mammals, Mfn2 also forms complexes that are capable of tether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
141
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(164 citation statements)
references
References 76 publications
11
141
0
Order By: Relevance
“…4d,e). VDAC and Mfn2 have both been reported to be ubiquitinated by Parkin during mitophagy, yet neither were affected by bortezomib or bafilomycin under the basal conditions of this experiment (32,40). These data suggest that Parkin-mediated lysosomal degradation of Mff is independent of mitophagy.…”
Section: Parkin Mediates Lysosomal Degradation Of Mff Independent Of mentioning
confidence: 51%
See 1 more Smart Citation
“…4d,e). VDAC and Mfn2 have both been reported to be ubiquitinated by Parkin during mitophagy, yet neither were affected by bortezomib or bafilomycin under the basal conditions of this experiment (32,40). These data suggest that Parkin-mediated lysosomal degradation of Mff is independent of mitophagy.…”
Section: Parkin Mediates Lysosomal Degradation Of Mff Independent Of mentioning
confidence: 51%
“…These data suggest that Parkin-mediated lysosomal degradation of Mff is independent of mitophagy. large-scale mitophagy (32,40,41). The degradation of Mff by Parkin under basal conditions, together with its inactivity toward other known substrates under the same conditions, suggest that Parkin-mediated degradation of Mff is a regulatory mechanism independent of mitophagy.…”
Section: Parkin Mediates Lysosomal Degradation Of Mff Independent Of mentioning
confidence: 99%
“…Miro1 is a crucial sensor for cytosolic calcium levels and is furthermore involved in the regulation of calcium homeostasis at the contact sites between mitochondria and the ER. MERCs are an emerging topic in the field of PD research and a number of PD-associated proteins were found to be involved in the regulation of MERCs, i.e., PINK1, Parkin, and LRRK2 [5][6][7]36]. Already in 2011, Kornmann and colleagues showed that Miro1 plays a role at the contact sites in mammalian Cos-7 cells [37].…”
Section: Discussionmentioning
confidence: 99%
“…PINK1, Parkin, LRRK2 and α-synuclein (α-syn) were recently found to be involved in the regulation of MERCs. Impaired function of these proteins caused fragmentation of the mitochondrial network, mitochondrial calcium dyshomeostasis and alterations of the amount of MERCs [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that XBP1s increases expression of PGC1α (Arensdorf et al, 2013;Cheang et al, 2017). Interestingly, PGC1α activates the PINK1/Parkin mitophagy pathway, which is involved in ubiquitination of Mfn2 (Chen and Dorn, 2013;Basso et al, 2018;McLelland et al, 2018). Similarly, a growing list of miRNA has been implicated in the downregulation of Mfn2 but it is not clear if they are expressed in hASM and whether XBP1 is involved in their regulation (Kuhn et al, 2010;Dileepan et al, 2016;Purohit et al, 2019).…”
Section: Mfn2 and Er Stress Responsementioning
confidence: 99%